The efficiency of eco-innovation: Systematic literature studies - Dawid Szutowski; Aleksandra Szulczewska-Remi; Piotr Ratajczak (Economic and Environmental Studies (E&ES), 2017)
Purpose: Eco-innovation appears to be at the very heart of the European Union policy. It is of crucial importance for both single companies and the whole economic systems. At the same time eco-innovation is driven by the countless factors. Thus the purpose of the present research was to indicate the determinants of the efficiency of eco-innovation. Design/methodology/approach: The research relied on the systematic literature studies performed with the use of SALSA (Search, AppraisaL, Synthesis, Analysis) method. It focused on the papers published between January 2000 and June 2016. A total of 469 publications were examined selected form Scopus database. The precise appraisal procedure allowed indicating the ones including the determinants of the efficiency of eco-innovation. Findings: The studies of literature allowed indicating a total of 24 determinants. Moreover the results indicate that the determinants of the efficiency of eco-innovation may be divided based on two criteria. The first includes costs-related and revenues-related determinants. The second includes strategic and operational levels. Research limitations/implications Together eleven publications were omitted in the research due to their incompletion or inaccessibility. Practical implications: Stimulating eco-innovation seems vital for all companies. Delivering a comprehensive set of the determinants of its efficiency will support executives in managing eco-innovation. Originality/value: The paper attempts to fulfil the research gap concerning the determinants of the efficiency of eco-innovation.
Keywords: O32; Q57; 330; eco-innovation; efficiency